1973
DOI: 10.1098/rspa.1973.0023
|View full text |Cite
|
Sign up to set email alerts
|

The electron distribution in silicon - II. Theoretical interpretation

Abstract: The absolute structure factors of silicon measured in Part I are examined in detail using Dawson’s structure factor formalism with recent theoretical estimates of free atom Hartree-Fock wavefunctions (Clementi 1965). It is not possible to describe the structure of silicon with only Kubic Harmonic expansions having physically reasonable coefficients. If the valence-shell form factor is radially compressed by 6.8% then we can obtain an excellent fit using only the third- and fourth-order Kubic Harmonics with amp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
48
0

Year Published

1974
1974
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(58 citation statements)
references
References 16 publications
10
48
0
Order By: Relevance
“…This new estimate agrees with the extremely accurate X-ray measurement of 0.0764(2)A by Aldred & Hart (1973).…”
Section: Note Added In Proofsupporting
confidence: 79%
“…This new estimate agrees with the extremely accurate X-ray measurement of 0.0764(2)A by Aldred & Hart (1973).…”
Section: Note Added In Proofsupporting
confidence: 79%
“…This B factor is difficult to reconcile with the expected value of $0.02 nm 2 (Reid & Pirie, 1980). The experimentally measured parameter on bulk Si of B $0.046 nm 2 , by Aldred & Hart (1973), represents the maximum value, because their experimental conditions were highly biased towards the core value. Reid & Pirie (1980) have critically reviewed the literature as well as having calculated this value for Si by numerous approaches, and concluded that B $0.02 nm 2 is the most likely value.…”
Section: Estimation Of the Temperature Factors In Simentioning
confidence: 95%
“…In strongly bonded Si the shell will be damped compared with the vibrations of the core, because it is linked via the bonding to other atoms (Reid & Pirie, 1980). The core Debye-Waller factor has been calculated and measured accurately, see for example the compilation and arguments in Reid & Pirie, and the measurements of Aldred & Hart (1973), who give a value close to the calculations at room temperature of B = 0.04613 nm 2 using high-order reflections; this value is therefore more closely related to the core. This puts an upper limit on the value of B under these conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Frozen phonon multislice simulations as implemented by Kirkland 31 were used for the standardless atom counting of the Pt nanocatalyst, the source size determination using GaN data and the Si dislocation distorted image series analysis. At 300 K, the root-mean-square displacements of Si, Ga and Pt atoms in the structures we studied are 0.076, 0.060 and 0.067 Å, respectively [32][33][34][35] .…”
Section: Methodsmentioning
confidence: 99%